Land and book : literature and land tenure in Anglo-Saxon England - Smith, Scott Thompson (Toronto Anglo-Saxon series., 2012)
Land and Book places a variety of texts in a dynamic conversation with the procedures and documents of land tenure, showing how its social practice led to innovation across written genres in both Latin and Old English.